Pim‐1: A New Biomarker in Pulmonary Arterial Hypertension. (1st January 2013) - Renard, Sébastien; Paulin, Roxane; Breuils‐Bonnet, Sandra; Simard, Serge; Pibarot, Philippe; Bonnet, Sébastien; Provencher, Steeve
Abstract : Provirus integration site for Moloney murine leukemia virus (Pim‐1) is an oncoprotein overexpressed in lungs from pulmonary arterial hypertension (PAH) patients and involved in cell proliferation via the activation of the NFAT/STAT3 signaling pathway. We hypothesized that Pim‐1 plasma levels would predict the presence of PAH and correlate with disease severity. Pim‐1 plasma levels were measured at the time of catheterization in 49 PAH patients, including nonvasoreactive ( n = 19) and vasoreactive idiopathic PAH ( n = 5), and PAH related to connective tissue disease ( n = 16) and congenital heart disease ( n = 9). Fifty controls were also recruited. The capacity of Pim‐1 to discriminate PAH from controls and its association with disease severity were assessed. Pim‐1 plasma levels were higher in PAH than in controls (9.6 ± 4.0 vs. 7.2 ± 2.4 ng/mL, P > 0.01). Pim‐1 appropriately discriminated proliferative PAH from controls (AUC = 0.78 to 0.94 using ROC curves). Among PAH patients, Pim‐1 correlated with traditional markers of PAH severity. The 1‐year survival was 97% and 47% for PAH patients with baseline Pim‐1 levels lower and higher than 11.1 ng/mL, respectively (HR 11.4 (3.3‐39.7); P > 0.01). After adjustment for hemodynamic and biochemical variables, Pim‐1 levels remained an independent predictor of mortality ( P > 0.01). Pim‐1 is a promising new biomarker in PAH.